Relationship between Chronic Intermittent Hypoxia and Intraoperative Mean Arterial Pressure in Obstructive Sleep Apnea Patients Having Laparoscopic Bariatric Surgery. (January 2015) - Turan, Alparslan; You, Jing; Egan, Cameron; Fu, Alex; Gazmuri, Ignazia; Khanna, Ashish; Eshraghi, Yashar; Ghosh, Raktim; Bose, Somnath; Qavi, Shahbaz; Arora, Lovkesh; Sessler, Daniel I.; et al.
<x xml:space="preserve">Abstract</x> Background: Recurrent nocturnal hypoxemia in obstructive sleep apnea enhances sympathetic function, decreases baroreceptor sensitivity, and weakens peripheral vascular responses to adrenergic signals. The authors hypothesized that the percentage of total sleep time spent at oxyhemoglobin saturation (SaO2) less than 90% and minimum nocturnal SaO2 on preoperative polysomnography are associated with decreased intraoperative mean arterial pressure. Methods: The authors examined the records of all patients who had laparoscopic bariatric surgery at Cleveland Clinic between 2005 and 2009 and an available polysomnography study. The authors assessed the relationships between the percentage of total sleep time spent at SaO2 less than 90% and minimum nocturnal SaO2, and the time-weighted average of mean arterial pressure. The authors used multivariable regression models to adjust for prespecified clinical confounders. Results: Two hundred eighty-one patients were included in the analysis. The average change in the time-weighted average of mean arterial pressure was −0.02 (97.5% CI, −0.08, 0.04) mmHg for each 1% absolute increase in the percentage of sleep time spent at SaO2 less than 90% (P = 0.50). The average change was −0.13 (97.5% CI, −0.27, 0.01) mmHg, for each 1% absolute decrease in the minimum SaO2 (P = 0.04 > significance criterion of 0.025, Bonferroni correction). An unplanned analysis estimated 1% absolute decrease in minimum SaO2 was associated with −0.22 (98.75% CI, −0.39, −0.04) mmHg, change in mean arterial pressure (P = 0.002) in the time period between endotracheal intubation and trocar insertion. Conclusion: Recurrent nocturnal hypoxemia in obstructive sleep apnea is not a risk marker for intraoperative hypotension.